Visual culture - Howells, Richard 1956-; Negreiros, Joaquim (Polity Press, 2012)
"The first part of the book is concerned with differing theoretical approaches to visual analysis, and includes chapters on iconology, form, art history, ideology, semiotics and hermeneutics. The second part shifts from a theoretical to a medium-based approach and comprises chapters on fine art, photography, film, television and new media. These investigate the complex relationship between reality and visual representation."--Book Jacket.